Smart Surfaces: Magnetically Switchable Light Diffraction through Actuation of Superparamagnetic Plate-Like Microrods by Dynamic Magnetic Stray Field Landscapes - Koch, Iris; Granath, Tim; Hess, Sebastian; Ueltzhoeffer, Timo; Deumel, Sarah; Caballero, Claudia Itzel Jauregui; Ehresmann, Arno; Holzinger, Dennis; Mandel, Karl (Advanced Optical Materials, 2018)
This work reports on a remotely controllable, all-magnetic reflective diffraction grating-like optical element for electromagnetic waves in the visible spectrum. The switchable grating is realized by the unique interplay between nanostructured superparamagnetic plate-like microrods and a magnetic stray field landscape generated by an engineered magnetic stripe domain pattern superimposed by a small external magnetic field. It is shown that the purposeful design of local magnetic field sources in such a continuous thin-film system enables a precise manipulation of the microrod alignment and, hence, dynamic control of the corresponding grating constant. It is demonstrated that the magnetic grating can be turned on and off due to disappearance of the engineered domain pattern when magnetically saturated. Moreover, the grating constant can be dynamically changed between two states when applying an AC external magnetic field. The experimental findings are corroborated by a theoretical model based on a quantitative description of the involved forces among the microrods and between microrods and substrate, respectively. These results therefore serve as a basis for smart surfaces with switchable diffraction properties on demand upon remote control.
CRIS-Team Scopus Importer:2020-04-02
Keywords: exchange bias; ion-bombardment-induced magnetic patterning; magnetic field landscape; microrods; smart materials